2013
DOI: 10.3323/jcorr.62.495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Various Types of Rust Powder on Iron Rust Formation

Abstract: When various types of rust powder coexist on the process of rust occurrence, the feature of the formed rust was investigated. As a result, the rust of the same cr ystalline morphology as the coexisted rust was formed preferentially. Moreover, the protective rust was formed by coexistence of rust homogeneous as the protective rust formed on weathering steel. Furthermore, by surface treatment of resin mixing the rust which promotes protective rust formation on weathering steel, the protective rust layer was form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The phenomenon is expected to be applicable to the droplets of saturated-NaCl solution in the rust layer because it is confirmed that the rust layer of a steel has a lot of pores of size in nm order. [22][23][24] Therefore, the following points are considered to be important to the atmospheric corrosion as;…”
Section: Effect Of Rh On Hydrogen Absorption Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon is expected to be applicable to the droplets of saturated-NaCl solution in the rust layer because it is confirmed that the rust layer of a steel has a lot of pores of size in nm order. [22][23][24] Therefore, the following points are considered to be important to the atmospheric corrosion as;…”
Section: Effect Of Rh On Hydrogen Absorption Ratementioning
confidence: 99%
“…Assuming that Kelvin equation is applicable to the saturated-NaCl solution, the tiny and saturated solution droplets exist in the rust layer, and a radius of the droplet may be or less than that limited by an RH. Since it is confirmed that there are a lot of pores with several orders of nm in rust layer, [22][23][24] it is guessed that the droplets are in the pores and on the substrate. Therefore, it is considered that increase in an RH induces increase in a radius of the saturated droplets, increase in a total contact area of the droplets to the substrate, increase in a corrosion rate multiplied by the area, and then increase in an i H .…”
Section: Effect Of Rh On Hydrogen Absorption Ratementioning
confidence: 99%